Molecular Mechanism of the UDP-Glucuronosyltransferase 2B20-like Gene (AccUGT2B20-like) in Pesticide Resistance of Apis cerana cerana - Cui, Xuepei; Wang, Chen; Wang, Xinxin; Li, Guilin; Liu, Zhenguo; Wang, Hongfang; Guo, Xingqi; Xu, Baohua (Frontiers in Genetics, 2020)
UDP-glucuronosyltransferases (UGTs), being multifunctional detoxification enzymes, play a major role in the process of resistance to various pesticides in insects. However, the mechanism underlying the molecular regulation of pesticide resistance remains unclear, especially in Apis cerana cerana (A. cerana cerana). In this study, all of the UGT genes in A. cerana cerana have been identified through the multiple alignment and phylogenetic analysis. Expression of AccUGT genes under different pesticides, and antioxidant genes after silencing of AccUGT2B20-like were detected by qRT-PCR. The resistance of overexpressed AccUGT2B20-like to oxidative stress was investigated by an E. coli overexpression system. Also, antioxidant-related enzyme activity was detected after silencing of AccUGT2B20-like gene. Expression pattern analysis showed that almost all UGT genes were upregulated under different pesticide treatments. This result indicated that UGTs participate in the detoxification process of pesticides. AccUGT2B20-like was the major gene because it was more highly induced than the others. Overexpression of AccUGT2B20-like in E. coli could effectively improve oxidative stress resistance. Specifically, silencing the AccUGT2B20-like gene increased oxidative stress by repressing the expression of oxidation-related genes, decreasing antioxidant-related enzyme activity, and increasing malondialdehyde concentration. Taken together, our results indicate that UGTs are involved in pesticide resistance, among which, AccUGT2B20-like contributes to the detoxification of pesticides by eliminating oxidative stress in A. cerana cerana. This study explains the molecular basis for the resistance of bees to pesticides and provides an important safeguard for maintaining ecological balance.